Penerapan Model Inkuiri Terbimbing untuk Meningkatkan Percaya Diri dan Prestasi Belajar Siswa - Supriyono Supriyono; Sunarti Sunarti (UM Purwokerto Press, 2022)
This research aimed to describe the application of guided inquiry model to improve student’s confidence in grade V SDN Kaligesingin science lesson, to describe the application of guided inquiry model to improve student achievement , and describing the effectiveness of the application of guided inquiry model to improve student achievement in grade V SDN Kaligesing in science learning. The design used was Mixed methods Research. The subjects of this research were the students of grade V SDNKaligesin. The data collection in this research was done by observation and test sheet. Based on the results of research conducted during three cycles, the results showed that the ability of teachers in applying guided inquiry model had increased during its implementation, student confidence also increased from cycle I to cycle III, in addition to student achievement had a significant increase of the cycle I until cycle III.